Pengaruh Human Relationship, Disiplin Kerja, Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Pegawai pada PT. Perkebunan Nusantara IV Medan - Putri Lestari Br. Aruan; Kristanty Marina Natalia Nadapdap; Junika Napitupulu (Universitas Methodist Indonesia, 2025)
This study aims to determine and analyze human relationships. Work discipline, work environment and workload simultaneously affect employee performance at PT. Perkebunan Nusantara IV Medan. This research method uses quantitative descriptive research. The sample in this study was 180 respondents. This study was tested using SPSS 25. The data analysis method used was multiple linear regression analysis. Based on the results of the t hypothesis test, it is known that human relationships partially have a positive and significant effect on employee performance, partially work discipline does not have a positive and insignificant effect on employee performance, partially the environment does not have a positive and insignificant effect on employee performance, and workload partially has a positive and significant effect on employee performance. The f test shows that simultaneously human relationships, work discipline, work environment and workload have a positive and significant effect on employee performance at PT. Perekbunan Nusantara IV Medan. Based on the R Square value, it shows that the variables of human relationship, work discipline, work environment and workload affect employee performance by 0.524 or 52.4% and the remaining 47.6% is the influence of other variables such as motivation, punishment and leadership variables which are not included as variables in this study.